Plasmonic effect for photoluminescence enhancement in graphene/Au/ZnO hybrid structures: dependence on the surface lateral period of the Au layer. (19th May 2021) - Dong, Zuoru; Chen, Peizong; Li, Shujie; Jiang, Zuimin; Xu, Fei
Abstract: The basic physics of the plasmonic effect of graphene in the UV region is fascinating but is not well understood. In this work, the influence of surface lateral period on the plasmonic effect of graphene for photoluminescence (PL) enhancement in graphene/Au/ZnO hybrid structures at a laser excitation wavelength of 325 nm is studied. In graphene/Au/ZnO hybrid structures, the Au layers act as corrugated surfaces, and their lateral period varies with the layer thickness. A reduction in PL intensity due to graphene was observed in the graphene/ZnO hybrid structure, and this was attributed to electron transfer from the ZnO to the graphene. The electron transfer was confirmed by a 10 cm −1 redshift for the 2D Raman peak of graphene in graphene/ZnO in comparison to that for graphene/SiO2 (300 nm)/Si. In contrast, an enhancement in PL intensity by the graphene was observed when an Au layer was inserted between the graphene and the ZnO, and the enhancement ratio strongly depended on the surface lateral period of the Au layer. This enhancement is explained by effective excitation of the plasmon in the graphene at the momentum matching condition while the corrugated Au surface provides effective momentum compensation for excitation of the plasmon by the incident light in the graphene.